Роль сигнальних пептидів у регуляції судинного тонусу в ґенезі гестаційної ендотеліопатії - Коньков, Д.Г. (Таврический медико-биологический вестник, 2013)
В статье представлены результаты исследования роли эндотелина-1 и С-натрийуретического пептида в регуляции сосудистого тонуса у беременных. Результаты работы позволяют рассматривать одновременное увеличение в крови эндотелина-1, С-натрийуретического пептида и увеличение их соотношения более 0,5 пг/мл/нг/мл, как прогностические маркеры дисфункции вазоконстрикторных и вазодилятирующих свойств эндотелия. Данное исследование свидетельствует о главенствующей роли регуляции сосудистого тонуса в генезе гестационной эндотелиопатии. Использование показателей сигнальных вазорегуляторных пептидов в клинической практике значительно расширят арсенал методов, применяемых для ранней диагностики акушерской патологии, поможет оценить эффективность проводимой терапии. The author presents the results of studying the role of endothelin-1 and C-natriuretic peptide in the vascular tone regulation for pregnant women. The investigation results give the basis for a conclusion that the simultaneous increase of content of endothelin-1 and C-natriuretic peptide in blood and their ratio increase to more than 0,5 pg/ml/ng/ml can be considered as the markers for prognosis of vasoconstrictor and vasodilatation dysfunctions of the endothelial properties. This study has demonstrated the leading role of the regulation of the vascular tone in the pathogenesis of gestational endotheliopathy. The use of signal vasoregulatory peptides as indicators in clinical practice will significantly expand the arsenal of methods used for early diagnosis of obstetric pathology and help to evaluate the therapy effectiveness.